Method to enhance the resolution of x-ray coherent diffraction imaging for non-crystalline bio-samples - Ti-Yen Lan; Po-Nan Li; Ting-Kuo Lee (New Journal of Physics, 2014)
To circumvent the problem of radiation damage when using an x-ray coherent diffraction imaging experiment to resolve the structure of biological samples, we propose a method to add objects made of heavy atoms with the bio-samples or we load the samples on a template made of heavy atoms. This template method is shown by a numerical simulation (including shot noise) to be able to resolve the structure of a virus better than without the template. A counter-intuitive result is obtained, where heavier templates have a better resolution, even if the diffraction intensity of the bio-sample is much smaller than the noise intensity. In addition, the method also helps to greatly increase the efficiency of phase retrieval. We also provide a way to estimate the error to be expected if a particular experimental setting were chosen once the charge ratio between the sample and the template is estimated. Hence, this method will also help experiments choose the optimal setting for the best resolution with minimal radiation damage.